2018
DOI: 10.1111/ina.12489
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of particle deposition around the cabin air supply nozzles of commercial airplanes using measured in-cabin particle emission rates

Abstract: Enhanced soiling on the surfaces around air supply nozzles due to particle deposition is frequently observed in commercial airliners. The problem is worsened by severe outdoor air pollution and flight delays in China. The particles in an aircraft cabin originate from both outdoor and in-cabin sources. This study conducted measurements on multiple commercial flights to obtain particle emission rates from in-cabin sources. Additional experiments on a retired MD-82 airplane provided justification of the in-flight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Lin et al also found that pressure dropped in all examined electret masks after ethanol decontamination. In another study, they examined the relative survival (RS) of Bacillus subtilis spores on N95 FFRs under worst-case temperature and relative humidity conditions and 70% ethanol resulted in 22% of RS in 24 h which was decayed from the initial RS of 73% [ 23 ]. The conclusion that may be drawn from the results of the studies above is that ethanol decontamination can effectively inactivate coronavirus on inanimate surfaces, but when applied to FFRs, it may lower biocidal efficacy and degrade the filter quality.…”
Section: Resultsmentioning
confidence: 99%
“…Lin et al also found that pressure dropped in all examined electret masks after ethanol decontamination. In another study, they examined the relative survival (RS) of Bacillus subtilis spores on N95 FFRs under worst-case temperature and relative humidity conditions and 70% ethanol resulted in 22% of RS in 24 h which was decayed from the initial RS of 73% [ 23 ]. The conclusion that may be drawn from the results of the studies above is that ethanol decontamination can effectively inactivate coronavirus on inanimate surfaces, but when applied to FFRs, it may lower biocidal efficacy and degrade the filter quality.…”
Section: Resultsmentioning
confidence: 99%
“…26 In a study of heating a contaminated mask for 15 min at 121°C at 103 kPa, there was near 100% sterilization of bacteria (using B. subtilis spores), but virus survival was not evaluated. 27 Steam alone is successful at decontaminating from avian coronavirus. 20 …”
Section: Resultsmentioning
confidence: 99%
“…They even proposed an emission rate of PM 10 per passenger of ~15 µg m −3 pax −1 during boarding/deplaning, and ~5-6 µg m −3 pax −1 while sitting. 20 Finally, passengers are also a source of bioaerosol.…”
Section: Cabin Air Pollutionmentioning
confidence: 99%
“…Cao et al recently showed a higher particle concentration in the cabin during boarding and deplaning of a commercial aircraft. They even proposed an emission rate of PM 10 per passenger of ~15 µg m −3 pax −1 during boarding/deplaning, and ~5–6 µg m −3 pax −1 while sitting 20 . Finally, passengers are also a source of bioaerosol.…”
Section: Introductionmentioning
confidence: 99%